Islam on Screen: Imaginary Realities and the Crisis of Spiritual Authenticity in the Digital Era - Mubarok, Asep Syahrul; Fatnanda, Ida (Rausyan Fikri Journal of Islamic Studies, 2025)
In today’s digital era, reality can be replaced by representations that are considered more real than reality itself. In the context of Islam, this phenomenon occurs when religious symbols and worship practices no longer refer to authentic meanings, but instead become objects of cultural and media consumption. This article aims to analyze how the concepts of simulacra and hyperreality work in the Islamic realm by examining concrete examples of popular religious phenomena on social media and how Islam views these phenomena. This article shows that in today's digital era, the religious experience of Muslims is often more influenced by images and representations than by the underlying spiritual substance. Based on the values contained in the verses of the Qur'an and the hadith, Muslims must be able to be critical and wise and carry out authentic religious practices (attached to the meaning of religion that should be). This research primarily focuses on theoretical analysis. Future research could utilize qualitative or quantitative methods to explore in more depth how simulacra and hyperreality actually shape the religious patterns of Muslim communities and how Islamic educational strategies can respond to these phenomena.